Controversies and insights into PTBP1-related astrocyte-neuron transdifferentiation: neuronal regeneration strategies for Parkinson’s and Alzheimer’s disease - Simon McDowall; Vaishali Bagda; Stuart Hodgetts; Frank Mastaglia; Dunhui Li (Translational Neurodegeneration)
Abstract Promising therapeutic strategies are being explored to replace or regenerate the neuronal populations that are lost in patients with neurodegenerative disorders. Several research groups have attempted direct reprogramming of astrocytes into neurons by manipulating the expression of polypyrimidine tract-binding protein 1 (PTBP1) and claimed putative converted neurons to be functional, which led to improved disease outcomes in animal models of several neurodegenerative disorders. However, a few other studies reported data that contradict these claims, raising doubt about whether PTBP1 suppression truly reprograms astrocytes into neurons and the therapeutic potential of this approach. This review discusses recent advances in regenerative therapeutics including stem cell transplantations for central nervous system disorders, with a particular focus on Parkinson’s and Alzheimer’s diseases. We also provide a perspective on this controversy by considering that astrocyte heterogeneity may be the key to understanding the discrepancy in published studies, and that certain subpopulations of these glial cells may be more readily converted into neurons.